2010
DOI: 10.1590/s1516-18462010005000096
|View full text |Cite
|
Sign up to set email alerts
|

Relação entre disfunção temporomandibular e alterações auditivas

Abstract: TEMA: o equilíbrio das estruturas e funções do sistema estomatognático depende do adequado funcionamento da Articulação Temporomandibular, e esta, por sua vez, precisa da oclusão dental correta para a realização das funções ao movimentar a mandíbula. O desequilíbrio muscular ou estrutural da Articulação Temporomandibular poderá acarretar em uma disfunção dessa articulação e causar sinais e sintomas diversos como manifestações auditivas do tipo zumbido e otalgia. OBJETIVO: realizou-se a revisão de literatura da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
9

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 15 publications
(21 reference statements)
1
4
0
9
Order By: Relevance
“…An author (24) confirmed that the incidence of middle-ear disorders is unlikely, as, in his study, all patients with TMD kept A-type tympanometric curves, matching the findings of the current study.…”
Section: Discussionsupporting
confidence: 89%
“…An author (24) confirmed that the incidence of middle-ear disorders is unlikely, as, in his study, all patients with TMD kept A-type tympanometric curves, matching the findings of the current study.…”
Section: Discussionsupporting
confidence: 89%
“…It is believed that this opening in the fossa allows the passage of fluid in the middle ear and mastoid to the temporomandibular joint 11 . Since individuals with cleft palate are more likely to experience otitis media with effusion, and the vast majority of this sample had abnormal middle ear, it would be expected that these disorders present in the temporomandibular region 14 . However, imaging studies and the clinical evaluation of ATM revealed that almost all individuals in the sample had no complaints, signs and symptoms related to TMJ disorders.…”
Section: Tubal Disfunction Temporomandibular Disordermentioning
confidence: 99%
“…It is believed that the opening present in articular fossa allows the passage of fluid from the middle ear and mastoid to the joint region of the temporomandibular joint 11 , and that there is a link between the stomatognathic system and the auditory system, which can be causes and consequences of temporomadibular dysfunctions 14,15 . As individuals with cleft palate exhibit significant possibility of developing otitis media with effusion 16 , the present study aimed to investigate the existence of temporomandibular disorders, having as a predisposing factor the tube dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…Multifatores são apontados como causas, sendo estes os distúrbios da oclusão e traumas que sobrecarregam a articulação temporomandibular, hábitos deletérios, próteses mal adaptadas ou restaurações, alterações musculares, problemas degenerativos, alterações funcionais, problemas emocionais e estresse 3 .…”
Section: Introductionunclassified